Upper bounds on second order operators, acting on metric function - Antoniouk, A.V. (Український математичний вісник, 2007)
We prove upper bounds on the general second order operator acting on metric function. The suggested approach does not use traditional formulas for deviations of geodesics and Jacobi fields construction and leads to the manifolds generalization of the classical coercitivity and dissipativity conditions for diffusion equations.